2022
DOI: 10.1186/s12913-022-07668-1
|View full text |Cite
|
Sign up to set email alerts
|

Voice-based control system for smart hospital wards: a pilot study of patient acceptance

Abstract: Background The smart hospital's concept of using the Internet of Things (IoT) to reduce human resources demand has become more popular in the aging society. Objective To implement the voice smart care (VSC) system in hospital wards and explore patient acceptance via the Technology Acceptance Model (TAM). Methods A structured questionnaire based on TAM was developed and validated as a research tool. Onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…While other studies have used voice-based approaches in other health settings 12,13 , to our knowledge, this is the first study to assess collecting self-reported epidemiology data with a voice-based system (a previous grant that sought to create a voice-based interface did not to our knowledge achieve this objective 14 ). Many more studies are needed to understand the strengths and limitations of different approaches to collect epidemiology data using voice, for example, with different voice-based systems (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While other studies have used voice-based approaches in other health settings 12,13 , to our knowledge, this is the first study to assess collecting self-reported epidemiology data with a voice-based system (a previous grant that sought to create a voice-based interface did not to our knowledge achieve this objective 14 ). Many more studies are needed to understand the strengths and limitations of different approaches to collect epidemiology data using voice, for example, with different voice-based systems (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…While other studies have used voice-based approaches in other health settings 12,13 , to our knowledge, this is the first study to assess collecting self-reported epidemiology data with a voicebased system (a previous grant that sought to create a voice-based interface did not to our knowledge achieve this objective 14…”
Section: Discussionmentioning
confidence: 99%
“…Although other studies have used voice-based approaches in other health settings [ 16 - 19 ], to the best of our knowledge, this is the first study to assess collecting self-reported epidemiology data with a voice-based system (to the best of our knowledge, a previous grant that sought to create a voice-based interface did not achieve this objective [ 20 ]). Furthermore, although our focus was on using this technology for collecting epidemiological data, the results of our study are likely to be useful more broadly, for example, to inform the development of technologies for personalized health care or commercial systems (collecting self-reported data to track behavior).…”
Section: Discussionmentioning
confidence: 99%
“…Smart hospitals are the main body of intelligent medical care, which can integrate various software and hardware to improve the efficiency of hospital services and management [ 3 ]. On this basis, the smart ward integrates the above technologies in the ward to achieve the purpose of intelligent management of patients, equipment, and ward software and hardware [ 4 ]. Smart ward is the core and focus of smart healthcare.…”
Section: Intelligent Intensive Care Unitmentioning
confidence: 99%